Cubic Perovskite ZnTiO3 Nanopowder as a Recyclable Heterogeneous Catalyst for the Synthesis of 1, 6‐Naphthyridines in Water. Issue 4 (15th January 2015) - Ray, Suman; Das, Paramita; Banerjee, Biplab; Bhaumik, Asim; Mukhopadhyay, Chhanda
Abstract Cubic perovskite ZnTiO3 nanopowder has been prepared by means of a sustainable sol–gel method. The nanopowder (12–20 nm) has been thoroughly characterized by N2 sorption analysis, high‐resolution (HR) TEM, X‐ray diffraction (XRD), X‐ray photoelectron spectroscopy (XPS), SEM, and FTIR analyses. The environmentally benign synthesis of highly substituted 1, 6‐naphthyridines catalyzed by ZnTiO3 nanopowder in aqueous media has been demonstrated. It requires two different catalytic functions, that is, an acid one, which is provided by TiIV ions, and a basic one, which is provided by the oxide ion incorporated within the ZnTiO3 metal oxide framework. 1, 6‐Naphthyridines are of tremendous biological importance, and this method is simple and environmentally friendly. The greenness of the process was satisfactorily established as water was exploited as the reaction medium and there was very high atom economy.